COVID-19 and stroke – Updated review - Pushpendra Nath Renjen; Dinesh Mohan Chaudhari; Anjali Mishra; Immia Bukhari (Apollo Medicine)
Although the precise incidence is not known, stroke is emerging as a complication of the COVID-19 pandemic. The clinical course of COVID-19 is most severe in elderly patients, in men, and in patients with comorbidities such as hypertension, diabetes, heart disease, and obesity, all risk factors for stroke. Severe acute respiratory syndrome coronavirus infection is linked to a prothrombotic state causing venous and arterial thromboembolism and elevated D-dimer levels. The occurrence of acute ischemic stroke at the time of this pandemic poses a great challenge regarding emergency treatment (particularly administering thrombolysis and performing thrombectomy) of acute stroke patients. In this article, we will review the pathophysiology and challenges in the management of COVID-19 infection-associated stroke.